Các nhân tố ảnh hưởng đến ý định liên kết giữa hộ nuôi với các tác nhân tham gia chuỗi cung ứng cá hồng Mỹ tại Việt Nam - Nguyen Thi , Nga; Ho Huy , Tuu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
This study aims to explain cooperative intention between farmers and other factors in red snapper chain in Vietnam. This study extends the theory of planned behavior (TPB) by integrating 5 variables including trust, cultural link, government policies, linked knowledge, and uncertainty of links to explain for the variables in the original planned behavior model as attitudes, social norms, perceived behavioral control, and cooperative intention. This study adopts partial least squares structural equation modeling (PLS-SEM) technique to test the reliability and validity of the measures based on a sample of 170 farmers in the farming area of red snapper in 5 provinces (Kien Giang, Ba Ria-Vung Tau, Khanh Hoa, Phu Yen, and Nghe An). The results indicate that all proposed hypotheses are supported by data. In the context of empirical studies in explaining cooperative motivation between factors in a product supply chain using TPB is scarce, this research result is a significant contribution in both academic and policy implications, especially in case of the supply chain of red snapper, a new farmed species.
Keywords: Supply chain; TPB; Cooperative intention; Red snapper; Vietnam